Trends in economic growth, poverty and energy in Colombia: Long-run and short-run effects (2011)
This research analyses the long run and short run relationships among economic growth, poverty and energy using the Colombian case. In this study, we use the time-series methodologies. The results regarding the relationship among economic growth, poverty and energy show that increases in gross domestic product and energy supply per capita should lead a decrease of poverty, which should demonstrate that access to modern and adequate energy services help to decrease poverty and to increase economic growth. Moreover, the improvements in energy efficiency have contributed to increase economic growth from an approach of sustainable development. These results are important for the adequate design, formulation and application of policies and strategies that encourage a better energy use to improve economic growth and decrease poverty, especially in developing countries.